Gelatin as a promising printable feedstock for microbial fuel cells (MFC). (19th January 2017) - Ieropoulos, Ioannis; Theodosiou, Pavlina; Taylor, Benjamin; Greenman, John; Melhuish, Chris
Abstract: The microbial fuel cell (MFC) is an energy transducer that can directly produce electricity from bacterial oxidation of organic matter. MFCs consist of two reaction chambers (anode and cathode) separated by a semipermeable membrane. This study describes the work carried out towards the optimization of critical MFC components, with 3D fabricated materials. The response of the optimized fuel cells, which were fed with soft materials such as gelatin, alginate and Nafion™, is also reported. The optimised components were the membrane and the cathode electrode. A conventional Nafion membrane was substituted with a custom made terracotta sheet and the electrode used was a single sheet of carbon veil coated with an activated carbon paste. The results showed that among the soft materials tested within the anodic chamber, gelatin performed the best; it also revealed that even after a 10-day starvation period gelatin demonstrated better longevity. These results show that MFCs have the potential to be 3D-printed monolithically using the EVOBOT platform. Highlights: Soft materials tested for the first time as feedstock in MFCs. Higher output from gelatin fed MFCs after constant feeding stopped. Detrimental effect of liquid Nafion to the microbial community. Potential implementation of the proof of concept to EVOBOT platform for 3D printed MFCs.